Malignant Brain Tumors State-of-the-Art Treatment - Moliterno Gunel, Jennifer; Piepmeier, Joseph M.; Baehring, Joachim M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text addresses all aspects of patient evaluation and care. This includes new findings in imaging that provide a better understanding of the extent of the lesion as well as its relationship with critical neuroanatomic function. The evolution of intraoperative imaging, functional brain mapping,and technology to identify tumor from brain is covered. This has significantly improved the ability of surgeons to more safely and aggressively remove tumors.More importantly, a better understanding of tumor biology and genomics has created an opportunity to significantly revise tumor classification and better select optimal therapy for individual patients. The text covers novel and innovative treatment options including immunotherapy, tumor vaccines, antiangiogenic agents,and personalized cancer treatment. In addition, novel agent delivery techniques are covered to offer the potential for increasing the effectiveness of treatment by delivering active agents directly where they are needed most. Malignant Brain Tumors: State-of-the-Art Treatment provides a comprehensive overview of treatment for malignant gliomas, and will prove useful by updating physicians on new therapeutic paradigms and what is on the horizon for the near future. This text will be informative for surgeons, oncologists, neurologists, residents and students who treat these patients,as well as those who are training for a career in managing patients with these challenging tumors. .
Part I: Molecular and Clinical Characterization of Gliomas -- The Use of Advanced Neuro-Imaging (fMRI, DTI/Tractography) in the Treatment of Malignant Gliomas -- Molecular Neuropathology and the Ontogeny of Malignant Gloimas -- Personalized Medicine through Advanced Genomics -- Part II: Surgery: Maximizing the Extent of Tumor Resection -- The Usefulness of Stereotactic Neuronavigation Along with Intraoperative Imaging in Malignant Brain Tumor Surgery -- Mapping the Brain for Primary Tumor Surgery -- Fluorescence-guided Resection of Malignant Gliomas -- The Rolse of Laser-Induced Thermal Therapy in the Management of Malignant Gliomas -- Part III: Adjuvant Therapies -- Current Standard Treatment Options of Malignant Glioma -- Targeting Aberrant Signaling Pathways -- Targeted Therapy of IDH1-mutated Tumors -- Antiangiogenic Therapy for Malignant Gliomas -- Immunotherapy for High-Grade Gliomas -- Novel Delivery Strategies -- Radiation Therapy for Malignant Gliomas: Current Options -- Glioma Radiosensitizers: Exciting New Developments and Directions -- Part IV: Tumor-Specific Approach: Oligodendroglioma (IDH1 mutated, 1p/19q deleted) -- Glioblastoma.
Keywords: Medicine; Neurosurgery; Surgical oncology; Medicine & Public Health; Neurosurgery; Surgical oncology